The effect of parity on the incidence of breast-feeding duration and its predictors among lactating mothers in East Gojjam Zone, North-west Ethiopia: community-based retrospective follow-up study - Tilahun Degu Tsega; Gashaw Melkie Bayeh; Ahmed Fentaw Ahmed; Zewdu Bishaw Aynalem; Almaw Genet Yeshiwas (BMC Pediatrics)
Abstract Background Over 25% of Ethiopian children under three years old have not been breastfed for two years or more. Previous literature has not identified the effect of parity on breastfeeding duration, and evidence regarding this issue in Ethiopia is limited. Therefore, this study aims to identify the effect of parity on the incidence of short breastfeeding duration among lactating mothers in the East Gojjam Zone, Northwest Ethiopia. Methods A community-based retrospective follow-up study was conducted in East Gojjam administration Zone. A total of 1190 mothers, with a response rate of 94.44%%, were participated from January-1 to February-30, 2023. A multistage stratified random sampling technique with proportional allocation was used to recruit study participants. Data were collected using kobo collect and then exported to Stata 17 for coding and analysis. Bi-variable and multivariable proportional Cox hazard regression was employed to identify predictor variables. Result The overall short breastfeeding incidence rate was 11.79 per 1000 (95% CI: 10.52, 13.22), for primiparous, 1.57 (95% CI: 1.02, 2.41) and multiparous mothers, 23.71 (95% CI: 21.06, 26.71) per 1000 person-months. The mean breastfeeding duration was 23.55 and 18.44 month among primiparous and multiparous mothers respectively. The overall proportion of short-breastfeeding duration was 24.62% (95%CI: 22.19%, 27.17%) and shows statistically significant variation between primiparous 3.69% (95%CI: 2.30%, 5.59%) and multiparous 43.73 % (95%CI: 39.79 %, 47.73%) mothers. Being multiparous were (AHR = 5.5, 95%CI: 3.44, 8.78), having poor wealth asset [primiparous: (AHR = 4.20, 95%CI: 1.07, 16.45), multiparous: (AHR = 1.89, 95%CI: 1.39, 2.59) and pooled: (AHR = 1.99, 95%CI: 1.47, 2.69)], and being unmarried [primiparous: (AHR = 5.68, 95%CI: 2.25, 14.31), multiparous: (AHR = 3.72, 95%CI: 2.73, 5.05) and pooled: (AHR = 4.15, 95% CI: 3.09, 5.57)]. Starting complimentary feeding <6 months and having >4 number of children were independent predictor for short breast-feeding duration. Conclusion The incidence of short breastfeeding practice was high and showed statistically significant variation between primiparous and multiparous mothers. Hence, the identified modifiable factors need to be the areas of intervention to increase the duration of breastfeeding for at least 24 months among the mothers.